Seasonal Variation in the Faecal Microbiota of Mature Adult Horses Maintained on Pasture in New Zealand - Fernandes KA; Gee EK; Rogers CW; Kittelmann S; Biggs PJ; Bermingham EN; Bolwell CF; Thomas DG (MDPI (Basel, Switzerland), 2021)
Seasonal variation in the faecal microbiota of forage-fed horses was investigated over a 12-month period to determine whether the bacterial diversity fluctuated over time. Horses (n = 10) were maintained on pasture for one year, with hay supplemented from June to October. At monthly intervals, data were recorded on pasture availability and climate (collected continuously and averaged on monthly basis), pasture and hay samples were collected for nutrient analysis, and faecal samples were collected from all horses to investigate the diversity of faecal microbiota using next-generation sequencing on the Illumina MiSeq platform. The alpha diversity of bacterial genera was high in all samples (n = 118), with significantly higher Simpson's (p < 0.001) and Shannon-Wiener (p < 0.001) diversity indices observed during the months when horses were kept exclusively on pasture compared to the months when pasture was supplemented with hay. There were significant effects of diet, season, and month (ANOSIM, p < 0.01 for each comparison) on the beta diversity of bacterial genera identified in the faeces. While there was some inter-horse variation, hierarchical clustering of beta diversity indices showed separate clades originating for samples obtained during May, June, and July (late-autumn to winter period), and January, February, and March (a period of drought), with a strong association between bacterial taxa and specific nutrients (dry matter, protein, and structural carbohydrates) and climate variables (rainfall and temperature). Our study supports the hypothesis that the diversity and community structure of the faecal microbiota of horses kept on pasture varied over a 12-month period, and this variation reflects changes in the nutrient composition of the pasture, which in turn is influenced by climatic conditions. The findings of this study may have implications for grazing management and the preparation of conserved forages for those horses susceptible to perturbations of the hindgut microbiota.
Keywords: Illumina MiSeq; bacteria; community ecology; diversity; faeces; horse; microbiota; next-generation sequencing; nutrient composition; pasture; ribosomal RNA gene; water-soluble carbohydrates